Comparison of the growth, fruit quality and physiological characteristics of cucumber fertigated by three different nutrient solutions in soil culture and soilless culture systems - Hamid Reza Roosta; Hossein Sharifi Azad; Seyed Hossein Mirdehghan (Scientific Reports)
Abstract Global warming and declining rainfall in recent years have led to increased water and soil salinity in Iran agricultural lands. To address these challenges, greenhouse cultivation, particularly soilless culture, emerges as a critical solution for mitigating the effect of soil salinity and water scarcity on vegetable plant production in Iran. The aim of this experiment was to compare the growth and physiological responses of cucumber plants cultivated in both soil and soilless systems, using three distinct nutrient solutions. With this purpose, a factorial experiment carried out with two factors of cultivation system (Soil cultivation and soilless cultivation) and nutrient solution (Hoagland, Papadopoulos, and Commercial) in a completely randomized design with three replications in greenhouse conditions. Cucumber seeds of the Nagene 792 F1 variety were sown in cultivation trays filled with a mixture of perlite and cocopeat (in a 1:1 ratio) to produce seedlings, which were then placed in the growbag with the same substrate in greenhouse environment. Additionally, in soil-based cultivation, the seeds were first sown in cultivation trays and then transferred to 10-L pots containing soil medium. The results of this study showed that the soilless culture system increased vegetative and reproductive characteristics such as plant height (13%), number of nodes (9.4%), internode distance, number of leaves, leaf area (31.45%), fresh and dry mass of shoots, fresh (21%) and dry (33%) mass of roots, number of flowers (9.4%), number of fruits (10.12%), and fruit diameter (19.5%) in cucumber plants. Soilless cultivation increased the yield per plant and cultivation area (52%). The photosynthetic pigments (27.5% and 49.18% for Chl a and b, respectively), and fruit quality traits including fruit appearance color (the components a (16.42%), b (19.44%), and L (1.87%), hue angle (32.74%), and chroma (15.13%)), total soluble solids (TSS) (7%) and vitamin C (31.85%) increased compared to soil-grown plants. The results showed that the percentage of flower fall in soil-grown plants was higher than the plants in soilless medium. Hoagland nutrient solution had a more significant effect on increasing these parameters than other nutrient solutions. Although, the highest flowering rate was observed in nutrient solution of Hochmat and Papadopoulos. Overall, soilless cultivation using the Hoagland nutrient solution significantly enhanced growth and yield characteristics, as well as both the quantitative and qualitative traits of the fruit and physiological characteristics, compared to the other treatment methods.